Lateral cephalometric analysis of the nasal morphology among Saudi adults - Aljabaa AH (Dove Medical Press, 2019)
Aljazi Hussain Aljabaa Division of Orthodontics, Department of Pediatric Dentistry and Orthodontics, College of Dentistry, King Saud University, Riyadh, Saudi Arabia Purpose: This study was designed to establish normal values for the nasal form and its relationship to the other cranial structures among male and female skeletal class I Saudi adults. The results of males and females were compared to each other and to the results of a previous study using the same analysis method.Patients and methods: Sixty-two lateral cephalometric radiographs of Saudi subjects (32 females and 30 males) were retrospectively retrieved from the orthodontic clinical data. Their ages ranged from 20 to 24 years old. All of the cephalometric radiographs were traced manually.Results: There were statistically significant differences between the Saudi males and females in the nasal length, nasolabial angle, horizontal distance from the nose tip to the incisal edge of the most prominent upper central incisor, and chin. The Saudi males had longer dorsa and increased vertical distances from the pronasale to the chin when compared to the females. The Saudi females had longer vertical distances from the pronasale to the upper lip and larger nasolabial angles when compared to the males. The Saudi males and females had longer noses, longer dorsa, more curved noses (larger supratip break angles), and increased horizontal distances between the nose tip and the chin when compared to a New Zealand sample. The New Zealand sample had increased nasolabial angles, increased nasal tip projection angles, noses significantly projected from the upper lip, the most prominent central incisors, and more prominent maxillae when compared to the Saudi sample.Conclusion: There were significant differences between the Saudi males and females, as well as between the Saudi sample and the New Zealand sample. These results suggest that both gender and ethnicity must be taken into account when establishing normal values for the nasal form and its relationship to the other cranial structures. Keywords: lateral cephalometry, nasal analysis, orthodontics, rhinoplasty